STRATEGI PENGEMBANGAN PEMASARAN PRODUK AGRIBISNIS ES PISANG IJO RAJA (Product Marketing Development Strategy of â€œEs King Banana Greenâ€ Agribusiness ) - Lungari, Clerry Nathania; Kumaat, Ribka M.; Talumingan, Celcius (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aims to determine the marketing strategy used by the "Es Pisang Ijo Raja" business. The types of data used in this study were primaryÂ and secondary data and SWOT analysis was applied. The results showed that the marketing strategy that must be implemented by the â€œEs Pisang Ijo Rajaâ€ business is an aggressive growth strategy by maintaining the taste and quality of the product and improving employee service to keep the demand for â€œEs Pisang Ijo Rajaâ€ high. In addition, it is necessary to maintain prices and always pay attention to packaging and product safety so that consumers would remain loyal. Keywords: strategy, strengths, opportunities, weakness, threats